SLOPE ANGLE ESTIMATION OF AMOANDA EAST PIT OF ABOSSO GOLD FIELDS, GHANA (Nigerian Journal of Technology, 2019)
This paper  determines  the possible modes of slope failure,  and the  effect of increasing the slope angle of the Amoanda East Pit Wall of Abosso Gold Fields Limited, Damang Mine by 5o and 10o from 70o because the designed slope angle (70o) will increase ore losses at Amoanda East. The methods employed include field geotechnical mapping of the slope face, and kinematic analysis using DIPS 6.0 software to analyse the modes of failures. Based on the kinematic analysis conducted using the slope angle per design (70o), it was found that the percentage of toppling, planar and wedge failures obtained were 20.05%, 5.41% and 0% respectively. Also, when the slope angle of Amoanda East Pit Wall was increased by 5o (75o) and 10o (80o), there was percentage increase in toppling and planar failures of (0.12 and 0.99) % and (2.59 and 4.18) % respectively, with no increment in wedge failure. Hence there is the possibility of planar and toppling failure with no wedge failure occurring at the Amoanda East. It is therefore recommended that, since the percentage increment in toppling and wedge were not significant when the slope angle was increased, the mine should continue to increase the slope angle by 5o and 10o from 70o.  http://dx.doi.org/10.4314/njt.v38i3.8